2022
DOI: 10.3390/toxics10080430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyphosate-Based Herbicide on Primary Production and Physiological Fitness of the Macroalgae Ulva lactuca

Abstract: The use of glyphosate-based herbicides (GBHs) worldwide has increased exponentially over the last two decades increasing the environmental risk to marine and coastal habitats. The present study investigated the effects of GBHs at environmentally relevant concentrations (0, 10, 50, 100, 250, and 500 μg L−1) on the physiology and biochemistry (photosynthesis, pigment, and lipid composition, antioxidative systems and energy balance) of Ulva lactuca, a cosmopolitan marine macroalgae species. Although GBHs cause de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 119 publications
2
13
0
Order By: Relevance
“…In addition, previous work showed that growth variations in P. tricornutum in response to a stressor are generally associated with impaired photosynthesis, and altered fatty acid content [27,28,47,48], often leading to reactive oxygen species (ROS) formation, which are the cellular response to stress signalling metabolites par excellence, responsible for opening and activating defence pathways. On the other hand, in U. lactuca, the negative effects of stress are not so visible, with the macroalgae showing tolerance to contamination and even the potential for remediation [40,93,94].…”
Section: Micro and Macroalgae Are Impacted By Environmentally Relevan...mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, previous work showed that growth variations in P. tricornutum in response to a stressor are generally associated with impaired photosynthesis, and altered fatty acid content [27,28,47,48], often leading to reactive oxygen species (ROS) formation, which are the cellular response to stress signalling metabolites par excellence, responsible for opening and activating defence pathways. On the other hand, in U. lactuca, the negative effects of stress are not so visible, with the macroalgae showing tolerance to contamination and even the potential for remediation [40,93,94].…”
Section: Micro and Macroalgae Are Impacted By Environmentally Relevan...mentioning
confidence: 99%
“…Photobiological assessments were performed through chlorophyll fluorescence analysis (PAM fluorometry) with a FluoroPen FP100 (Photo System Instruments, Drásov, Czech Republic), on a 1 mL cuvette (for P. tricornutum) or with leaf clips (for U. lactuca), in darkadapted samples. The OJIP test was used to determine the chlorophyll transient light curves [40,47,48,54], from which the photochemical parameters (Table 1) were obtained according to this method and the equations provided in [55][56][57].…”
Section: Chlorophyll a Pulse Amplitude Modulated (Pam) Fluorometrymentioning
confidence: 99%
See 3 more Smart Citations